Taguchi method approach on effect of lubrication condition on surface roughness in milling operation - Mohamad Syahmi, Shahrom; Nafrizuan, Mat Yahya; Ahmad Razlan, Yusoff (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.